The Effect of Nanofluid Volume Concentration on Heat Transfer and Friction Factor inside a Horizontal Tube - K., Kadirgama; Hussein, Adnan M.; R. A., Bakar; Sharma, Korada Viswanatha (Hindawi Publishing Corporation, 2013)
The additives of solid nanoparticles to liquids are significant enhancement of heat transfer and hydrodynamic flow. In this study, the thermal properties of three types of nanoparticles (Al2O3, TiO2, and SiO2) dispersed in water as a base fluid were measured experimentally. Forced convection heat transfer turbulent flow inside heated flat tube was numerically simulated. The heat flux around flat tube is 5000W/m2 andReynolds number is in the range of 5×103 to 50×103. CFD model by finite volume method used commercial software to find hydrodynamic and heat transfer coefficient. Simulation study concluded that the thermal properties measured and Reynolds number as input and friction factor and Nusselt number as output parameters. Data measured showed that thermal conductivity and viscosity increase with increasing the volume concentration of nanofluids with maximum deviation 19% and 6%, respectively. Simulation results concluded that the friction factor and Nusselt number increase with increasing the volume concentration. On the other hand, the flat tube enhances heat transfer and decreases pressure drop by 6% and −4%, respectively, as compared with circular tube. Comparison of numerical analysis with experimental data available showed good agreement with deviation not more than 2%